Mechanical thrombectomy failure in anterior circulation strokes: Outcomes and predictors of favorable outcome. (18th June 2022) - Marnat, Gaultier; Gory, Benjamin; Sibon, Igor; Kyheng, Maeva; Labreuche, Julien; Boulouis, Grégoire; Liegey, Jean‐Sebastien; Caroff, Jildaz; Eugène, François; Naggara, Olivier; Consoli, Arturo; Mazighi, Mikael; et al.
Abstract: Background and purpose: Despite continuous improvement and growing knowledge in the endovascular therapy of large vessel occlusion stroke (LVOS), mechanical thrombectomy (MT) still fails to obtain satisfying intracranial recanalization in 10% to 15% of cases. However, little is known regarding clinical and radiological outcomes among this singularly underexplored subpopulation undergoing failed MT. We aimed to investigate the outcome after failed MT and identify predictive factors of favorable outcome despite recanalization failure. Methods: We conducted a retrospective analysis of consecutive patients prospectively included in the ongoing observational multicenter Endovascular Treatment in Ischemic Stroke registry from January 2015 to September 2020. Patients presenting with anterior circulation LVOS treated with MT but experiencing failed intracranial recanalization defined as final modified Thrombolysis In Cerebral Infarction (mTICI) score of 0, 1 and 2a were included. Clinical and radiological outcomes were assessed along with the exploration of predictive factors of Day‐90 favorable outcome. Results: The study population comprised 533 patients. Mean age was 68.8 ± 16 years, and median admission National Institutes of Health Stroke Scale (NIHSS) and Alberta Stroke Program Early Computed Tomography Score (ASPECTS) were 17 (IQR 12–21) and 7 (IQR 5–8), respectively. Favorable outcomes were observed in 85 patients (18.2%) and 186 died (39.0%). The rate of symptomatic intracranial hemorrhage was 14.1%. In multivariable analysis, younger age (odds ratio [OR] 0.96, 95% CI 0.94–0.98, p < 0.001), a lower admission NIHSS (OR 0.87, 95% CI 0.83–0.91, p < 0.001), a lower number of MT passes (OR 0.77, 95% CI 0.77–0.87, p < 0.001), a lower delta ASPECTS between initial and Day‐1 imaging (OR 0.83, 95% CI 0.71–0.98, p = 0.026) and stroke etiology [significant difference among etiological subtypes ( p = 0.024) with a tendency toward more favorable outcomes for dissection (OR 2.01, 95% CI 0.71–5.67)] were significantly associated with a 90‐day favorable outcome. Conclusions: In this large retrospective analysis of a multicenter registry, we quantified the poor outcome after MT failure. We also identified factors associated with favorable outcome despite recanalization failure that might influence therapeutic management.